PO 8544 Use of Xpert MTB/RIF assay and FDA microscopy relative to monthly cultures in monitoring multidrug-resistant tuberculosis patients in bamako, mali. (24th April 2019) - Diarra, Bassirou; Aissata, B; Decroo, Tom; Keita, Marie L; Degoga, Boureima; Diallo, Fatimata; Fane, Bintou; Coulibaly, Gagni; Baya, Bocar; Somboro, Amadou; Dit Sadio Sarro, Yeya; Orsega, Suzanne; et al.
Abstract : Introduction: Xpert MTB/RIF assay is used extensively for the detection of rifampicin-resistant TB (RR-TB). RR-TB treatment monitoring is culture-based, although, in resource-limited settings, access to TB culture is poor. Alternative methods are needed. We therefore conducted a pilot study to determine the performance of fluorescein di-acetate FDA vital staining, a microscopy-based test that shows viable bacilli, and Xpert threshold cycle value (Ct) changes when assessing culture conversion at the end of the intensive phase of RR-TB treatment. Methods: Between December 2015 and April 2018, we prospectively followed patients with RR-TB during the 6-month intensive phase of a 21-month standardised WHO treatment regimen. Sputum was collected and tested monthly with Auramine, FDA, Xpert MTB/RIF, and culture (Manual MGIT). Culture was considered to have converted to negative when two consecutive cultures, taken at least 30 days apart, were negative, including at least one culture between 4–6 months of treatment. Results: Forty-one patients were included in this study, 80% were male and 7% were HIV-co-infected. Conversion could not be assessed in 12 (29%) patients. Among the remaining 29 patients, 9 (31%) converted, and 11 (38%) did not convert. All 9 who converted on culture had a negative FDA, and most (6) had a Ct trend that showed a reduction of excreted DNA (increasing Ct trend). Three of these were still positive on Auramine (excretion of dead bacilli?). Of 11 patients with positive cultures, 8 tested negative on FDA, 5 tested 'MTB not detected' on Xpert MTB/RIF, and another 2 showed a reduction of excreted DNA. Conclusion: Results from culture, FDA, and Xpert MTB/RIF provide similar results among converters but contrasting results among non-converters. Longer follow-up time is needed to assess the value of these tests to predict treatment outcome.